Symptoms of PTSD in Frontline Journalists: A Retrospective Examination of 18 Years of War and Conflict. (September 2018) - Feinstein, Anthony; Osmann, Jonas; Patel, Viral
Objective: The objective of the current study was to determine the frequency and severity of symptoms of posttraumatic stress disorder (PTSD) in journalists covering conflict. Methods: PTSD data (Impact of Event Scale–Revised) collected over an 18-year period from 684 conflict journalists were analyzed retrospectively for frequency and severity of reexperiencing, avoidance, and arousal symptoms. Conflicts covered were civil wars in the Balkans ( n = 140 journalists), 9/11 attack in New York City ( n = 46), Iraq war ( n = 84), Mexico drug wars ( n = 104), civil war in Syria ( n = 59), Kenya election violence/Al-Shabab terror ( n = 57), state-sanctioned media intimidation in Iran ( n = 114), and the current migration crisis in Europe ( n = 80). Results: The mean age of the sample was 38.59 (SD = 8.35) years, 461 (67%) journalists were men, and the mean duration of conflict work was 13.42 (SD = 7.74) years. The 5 most frequently endorsed symptoms were in the reexperiencing/intrusion category. Mean intrusion (1.31, SD = 0.97), avoidance (1.08, SD = 0.89), and arousal (1.07, SD = 0.96) scores for the entire sample were in the mild range. Being female and less educated independently predicted PTSD symptoms. Conclusions: PTSD phenomenology in a group of conflict journalists with well over a decade of frontline experience is dominated by reexperiencing symptoms. While symptom severity is for the most part mild, group means can obscure those individuals with significantly more severe difficulties.